Recommendations for Measuring the Electrically Evoked Compound Action Potential in Children With Cochlear Nerve Deficiency. Issue 3 (May 2020) - He, Shuman; Chao, Xiuhua; Wang, Ruijie; Luo, Jianfen; Xu, Lei; Teagle, Holly F. B.; Park, Lisa R.; Brown, Kevin D.; Shannon, Michelle; Warner, Cynthia; Pellittieri, Angela; Riggs, William J.
Abstract : Objectives: This study reports a method for measuring the electrically evoked compound action potential (eCAP) in children with cochlear nerve deficiency (CND). Design: This method was developed based on experience with 50 children with CND who were Cochlear Nucleus cochlear implant users. Results: This method includes three recommended steps conducted with recommended stimulating and recording parameters: initial screen, pulse phase duration optimization, and eCAP threshold determination (i.e., identifying the lowest stimulation level that can evoke an eCAP). Compared with the manufacturer-default parameters, the recommended parameters used in this method yielded a higher success rate for measuring the eCAP in children with CND. Conclusions: The eCAP can be measured successfully in children with CND using recommended parameters. This specific method is suitable for measuring the eCAP in children with CND in clinical settings. However, it is not suitable for intraoperative eCAP recordings due to the extensive testing time required.